Effect of Trastuzumab Deruxtecan on QT/QTc Interval and Pharmacokinetics in HER2‐Positive or HER2‐Low Metastatic/Unresectable Breast Cancer. Issue 1 (18th October 2022) - Shimomura, Akihiko; Takano, Toshimi; Takahashi, Shunji; Sagara, Yasuaki; Watanabe, Junichiro; Tokunaga, Eriko; Shinkai, Tetsu; Kamio, Takahiro; Kikumori, Kunika; Kamiyama, Emi; Fujisaki, Yoshihiko; Saotome, Dan; et al.
Abstract : HER2‐targeted anticancer therapies may be associated with cardiovascular adverse events. This study evaluated effects of the HER2‐targeted antibody–drug conjugate trastuzumab deruxtecan (T‐DXd, DS‐8201a) on QT/QTc interval and its pharmacokinetics. Patients with heavily pretreated, metastatic HER2‐expressing breast cancer were enrolled at seven study sites in Japan. T‐DXd was administered intravenously at 6.4 mg/kg on day 1 of each 21‐day cycle. Primary end points were baseline‐adjusted QTcF interval and pharmacokinetics parameters. Key secondary end points included safety events, serum concentration of T‐DXd and DXd at the time of electrocardiographic measurements, and antitumor activity parameters. Among 51 total patients, 47 (92.2%) had HER2‐low breast cancer (immunohistochemistry 1+ or 2+ and in situ hybridization–negative/equivocal/missing). Pharmacokinetic parameters after a single dose of T‐DXd were consistent with previous studies. After multiple doses, T‐DXd showed moderate accumulation (accumulation ratio (cycle 3/cycle 1), 1.35), but DXd showed minimal accumulation (1.09). The upper bound of the 90% confidence interval for mean ΔQTcF interval was < 10 ms at all timepoints, and at mean maximum serum concentration was also < 10 ms. Based on concentration‐QT analysis, ΔQTcF increased with increasing concentrations of T‐DXd and DXd. No clinically meaningful QTcF prolongation was observed. T‐DXd had a manageable safety profile and showed antitumor activity in HER2‐low breast cancer. In this study, a T‐DXd dose of 6.4 mg/kg, higher than the 5.4‐mg/kg dose currently approved for breast cancer, was not associated with clinically relevant QTcF prolongation in heavily pretreated patients with HER2‐expressing metastatic breast cancer. This study adds to our understanding of T‐DXd for treatment of HER2‐low breast cancer.